2017
DOI: 10.1111/ped.13265
|View full text |Cite
|
Sign up to set email alerts
|

Is colchicine more effective to prevent periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis episodes in Mediterranean fever gene variants?

Abstract: This study has involved the largest number of PFAPA syndrome patients in the literature. It is particularly important to assess and to demonstrate the high rate of response to colchicine prophylaxis in PFAPA syndrome patients, especially those with MEFV variant. On blood screening, neutrophilia associated with monocytosis and low procalcitonin could contribute to diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 27 publications
4
41
0
7
Order By: Relevance
“…Concurrent and FMF and PFAPA syndrome have been reported frequently [ 30 , 31 ]. Evidence shows that colchicine is more efficient in PFAPA patients with underlying of MEFV mutation [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent and FMF and PFAPA syndrome have been reported frequently [ 30 , 31 ]. Evidence shows that colchicine is more efficient in PFAPA patients with underlying of MEFV mutation [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in the literature have reported an increased frequency of Mediterranean Fever ( MEFV ) gene mutations in patients with PFAPA syndrome. The frequency of the MEFV mutations in patients with PFAPA syndrome is reported to be 8%-66% ( 8 , 12 , 13 , 14 , 15 ). It has been reported that patients with PFAPA having MEFV mutations have shorter episodes, longer inter-episodic intervals, and lower corticosteroid dose requirement for the disease attacks cessation ( 16 , 17 , 18 ).…”
Section: Periodic Fever Aphthous Stomatitis Pharyngitis Adenitis Smentioning
confidence: 99%
“…Notably, being responsive to steroids can be accepted as a clue for diagnosis of PFAPA syndrome and trying the steroid treatment in patients with PFAPA syndrome suspicion may be logical. Colchicine has been shown to be effective in reducing the frequency of the episodes, with a more prominent effect in patients with MEFV mutation in some studies ( 11 , 14 , 15 ). Therefore, colchicine should be considered before performing tonsillectomy in a certain percent of PFAPA patients, especially those from regions endemic for FMF.…”
Section: Periodic Fever Aphthous Stomatitis Pharyngitis Adenitis Smentioning
confidence: 99%
“…Colchicine 1 mg/day was well tolerated and effective in prophylaxis of attacks, although it had to be given systematically as after a 10-week pause symptoms reappeared. Data published mainly from pediatric populations suggest that colchicine may be a treatment option [2426]. Colchicine significantly prolonged the interval between episodes [24, 26].…”
Section: Discussionmentioning
confidence: 99%